2020
DOI: 10.2147/pgpm.s228709
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Pharmacogenomic Dissection of a Rosuvastatin-Induced Rhabdomyolysis Case Evokes the Polygenic Nature of Adverse Drug Reactions</p>

Abstract: Rosuvastatin, is a widely-used statin for the treatment of hypercholesterolemia and the prevention of cardiovascular diseases. Although rosuvastatin is well tolerated, about 3/10.000 patients can suffer severe myopathy. Rhabdomyolysis is a severe medical condition that causes injury to the skeletal muscle, electrolyte imbalances, acute renal failure and extreme creatine kinase (CK) elevation. Little is known regarding the molecular involvement of rosuvastatin-induced rhabdomyolysis (RIR). It has been demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In the literature, we found a total of 11 reported cases of rhabdomyolysis during concomitant treatment with ticagrelor and rosuvastatin (Table S4). 2–12 The patients (7 female, 4 male) were aged 49–87 years. The daily dose of rosuvastatin was 20–40 mg, and daily dose of ticagrelor 90–180 mg. Time to rhabdomyolysis onset from the start of concomitant medication was 2 weeks to 8 months (median 1.75 months).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, we found a total of 11 reported cases of rhabdomyolysis during concomitant treatment with ticagrelor and rosuvastatin (Table S4). 2–12 The patients (7 female, 4 male) were aged 49–87 years. The daily dose of rosuvastatin was 20–40 mg, and daily dose of ticagrelor 90–180 mg. Time to rhabdomyolysis onset from the start of concomitant medication was 2 weeks to 8 months (median 1.75 months).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, we found a total of 11 reported cases of rhabdomyolysis during concomitant treatment with ticagrelor and rosuvastatin (Table S4). [2][3][4][5][6][7][8][9][10][11][12] The patients (7 female, 4 male) were aged 49-87 years.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although usually well‐tolerated, rosuvastatin can cause muscle symptoms of varying severity, especially at higher doses 1 . Previously published case reports have suggested that concomitant use of rosuvastatin and the platelet‐inhibitor ticagrelor may have led to severe, even fatal, cases of rosuvastatin‐induced rhabdomyolysis 2–13 . Because the risk of rosuvastatin‐induced myotoxicity is concentration‐dependent, the rhabdomyolysis cases suggest a potential pharmacokinetic drug–drug interaction between ticagrelor and rosuvastatin.…”
mentioning
confidence: 99%
“…led to severe, even fatal, cases of rosuvastatin-induced rhabdomyolysis. [2][3][4][5][6][7][8][9][10][11][12][13] Because the risk of rosuvastatin-induced myotoxicity is concentration-dependent, the rhabdomyolysis cases suggest a potential pharmacokinetic drug-drug interaction between ticagrelor and rosuvastatin.…”
mentioning
confidence: 99%